Diagnosis of general agricultural problems of farmers through Village level Participatory Approach in Mahboobnagar district of Andhra Pradesh - M. Suryamani, (Journal of Agricultural Extension Management, 2025)
A major challenge in Indian agricultural development is to meet the food needs and need for raw material of the country, which can be achieved through planned development activity. People participation and partnership play a vital role in its achievement. Farmers are the backbone of agricultural development, who performs different farming activities from seed to seed. Existing Research and Extension systems operate largely in a top down manner. Usually scientists themselves decide the research agenda, which is often based upon their limited exposure to the real problems faced by farmers. The involvement of extension personnel and farmers in the above process is limited and passive